Innumeracy Mathematical Illiteracy and Its Consequences - John Allen Paulos (London Penguin Books Ltd, 2009)
Why do even well-educated people often understand so little about maths - or take a perverse pride in not being a 'numbers person'? In his now-classic book "Innumeracy", John Allen Paulos answers questions such as: why is following the stock market exactly like flipping a coin; how big is a trillion; how fast does human hair grow in mph; and, can you calculate the chances that a party includes two people who have the same birthday. Paulos shows us that by arming yourself with some simple maths, you don't have to let numbers get the better of you.